The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/1066480714529742
|View full text |Cite
|
Sign up to set email alerts
|

Relational Dynamics of Swinging Relationships

Abstract: This exploratory study used qualitative methods to gain a richer understanding of the relational dynamics in modern swinging relationships. Swinging was defined at the onset of the study as sexual activities that married couples engage in with people other than their spouses. Twenty people (10 couples) volunteered and were interviewed using computer-mediated communication. Symbolic interactionism provides the theoretical framework for the study. Within the construct of relational dynamics, themes of power and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…For example, the questions on prioritizing one’s primary relationship by avoiding emotional relationships with those outside it suggested a level of attachment within the primary relationship (as noted by Giddens, and Moors et al, ). The ability of the men, in particular, to agree with the rules presented in the survey also suggests the interaction effect discussed in previous research (e.g., Vaillancourt and Few‐Demo, ). Finally, the emphasis on privacy while also engaging in non‐normative behaviour reinforces the challenge the swinging population is facing with balancing societal and personal norms (as noted by Edgar, ).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…For example, the questions on prioritizing one’s primary relationship by avoiding emotional relationships with those outside it suggested a level of attachment within the primary relationship (as noted by Giddens, and Moors et al, ). The ability of the men, in particular, to agree with the rules presented in the survey also suggests the interaction effect discussed in previous research (e.g., Vaillancourt and Few‐Demo, ). Finally, the emphasis on privacy while also engaging in non‐normative behaviour reinforces the challenge the swinging population is facing with balancing societal and personal norms (as noted by Edgar, ).…”
Section: Discussionsupporting
confidence: 81%
“…The spontaneity of engaging in sex with others varies, so rules about boundaries are relatively flexible, while rules focused on preventing hostile, uncomfortable or unhealthy situations are impermeable (Frank, 2013;Harviainen and Frank, 2016). Regardless, these explicit and implicit rules are vital to the health of the primary relationship and have been a consistent finding for researchers (Bentzen and Traeen, 2014;Bergstrand and Sinski, 2010;Vaillancourt and Few-Demo, 2014).…”
Section: Summary Of the Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…This is not to suggest that all heterosexuals are tied to a traditional or structured conception of marital monogamy. Quite the contrary, research demonstrates that some heterosexuals are active participants in nontraditional sexual arrangements, including polyamorous groups; swingers networks; and bondage and discipline, dominance and submission, sadism and masochism (BDSM) communities that decouple monogamous norms and practices from marital status (Damon, ; de Visser & McDonald, ; Gould, ; Vaillancourt & Few‐Demo, ; Weiss, ). Nevertheless, in the present study, most heterosexuals remained beholden to a tradition of marital monogamy, both as a personal ideal and a marital practice.…”
Section: Discussionmentioning
confidence: 99%
“…Despite agreeing boundaries at the outset seemingly the norm, qualitative research suggests that rules regarding condom use in swinging encounters are less frequently established and/or adhered to 8. Perhaps unsurprising, studies have reported that only a small minority of swingers use condoms regularly or consistently 10 11. When discussed, the decision of whether or not to use condoms is said to depend on various factors, including whether the couples have had previous encounters together (although Kimberly and Hans found that having regular or repeat encounters with other swingers was rare, reflecting how variety is often the raison d'etre for swinging) and their knowledge of the extent to which the other couple engage in swinging.…”
mentioning
confidence: 99%